2021
DOI: 10.2185/jrm.2020-046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of puerperal hematoma: a retrospective study

Abstract: Objective: To evaluate the characteristics and risk factors of puerperal hematoma. Materials and Methods: Data from the medical records of 2,776 women, who delivered vaginally between January 2008 and December 2017 in the authors’ hospital, were analyzed retrospectively. Results: Primigravida status was considered to be a significant risk factor. Among women with multigravida status, maternal age, instrumental delivery, and episiotomy were considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The median time to detect formation of a hematoma is 6 h postpartum [ 6 ], while the most common presenting sign of a hematoma is pain within 24 h of delivery [ 2 , 3 ]. One retrospective study found that 46.2% of puerperal hematomas were associated with severe pain, and 61.5% of the hematomas were detected within 2 h of delivery [ 7 ]; 61.5% of cases had the hematoma on the right side [ 7 ]. Delayed detection of a vascular injury could be due to pressure necrosis, while immediate detection is seen with direct vessel injury [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The median time to detect formation of a hematoma is 6 h postpartum [ 6 ], while the most common presenting sign of a hematoma is pain within 24 h of delivery [ 2 , 3 ]. One retrospective study found that 46.2% of puerperal hematomas were associated with severe pain, and 61.5% of the hematomas were detected within 2 h of delivery [ 7 ]; 61.5% of cases had the hematoma on the right side [ 7 ]. Delayed detection of a vascular injury could be due to pressure necrosis, while immediate detection is seen with direct vessel injury [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management involves minimal additional treatment measures [ 15 ]. One retrospective study found that 53.8% of hematomas were ≥ 5 cm in size [ 7 ]. In contrast, larger (>12 cm) hematomas, continuously expanding hematomas, or those large enough to cause either urologic or neurologic symptoms may require management with surgical exploration or vessel ablation through interventional radiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ]. Hematoma in the episiotomy site is another uncommon complication due to episiotomy [ 6 , 7 ]. Also, it could be more common and expanded in patients with underlying diseases, such as coagulation disorders [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Puerperal genital hematoma (PGHA) is an infrequent but a serious obstetrical complication associated with delivery. Over the previous decade, the incidence of PGHA has been documented to range from around 1 in 1500 to 1 in 210 1–3 …”
Section: Introductionmentioning
confidence: 99%